2011
DOI: 10.1103/physreve.83.017301
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of magnetically interacting cubes by a turbulent fluid flow

Abstract: Previous work (e.g. [1], [2]) has demonstrated that combining mechanical vibration with magnetic interactions can result in the self assembly of complex structures, albeit at low yield. Here we introduce a system where the yield of self assembled structures is quantitatively predicted by a theoretical analysis. Millimeter sized magnetic blocks, designed to form chains as their minimal energy state, are placed in a turbulent fluid flow. The distribution of chain lengths that form is quantitatively consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Other forms of active matter range from assemblies of entire microorganisms 1 to collections of artificial microscopic swimmers which are self-propelled 2,3 and turbulently agitated active suspensions on the colloidal scale. 4 In this Communication, we show that the steady-state statistical mechanics of these diverse out-of-equilibrium forms of active matter as well as their low-frequency fluctuations and responses can be described using the concept of an effective temperature. The notion of effective temperature has been useful in describing passive glassy systems, 5 weakly driven systems such as gently sheared supercooled liquids and glasses 6,7 and vibrated granular matter, 8 driven vortex matter, 9,10 as well as in approximate theories and simulations of active biological matter.…”
mentioning
confidence: 94%
“…Other forms of active matter range from assemblies of entire microorganisms 1 to collections of artificial microscopic swimmers which are self-propelled 2,3 and turbulently agitated active suspensions on the colloidal scale. 4 In this Communication, we show that the steady-state statistical mechanics of these diverse out-of-equilibrium forms of active matter as well as their low-frequency fluctuations and responses can be described using the concept of an effective temperature. The notion of effective temperature has been useful in describing passive glassy systems, 5 weakly driven systems such as gently sheared supercooled liquids and glasses 6,7 and vibrated granular matter, 8 driven vortex matter, 9,10 as well as in approximate theories and simulations of active biological matter.…”
mentioning
confidence: 94%
“…Exciting ideas exist to let particles assemble by themselves [Whitesides and Grzybowski, 2002]. Magnetic interaction are excellently suited to investigate self-assembly of large scale prototypes of micro systems [Ilievski et al, 2011a;Shetye et al, 2008].…”
Section: Magnetostatic Interactionsmentioning
confidence: 99%
“…Stambaugh et al (2003) reported self-assembled 2D structures of centimetre-sized spherical particles with internal magnets that were shaken vertically, and observed different resulting structures that were based on particle concentration and magnet shape. Ilievski et al (2011b) demonstrated self-assembly of centimetre-sized magnetic cubes into chains in a turbulent flow by submerging them in a rotating reactor filled with water, this way introducing eddy flows as a disturbing energy. They also introduced the concept of effective temperature, describing the motion of particles as if Brownian by nature.…”
mentioning
confidence: 99%
“…Smart particles have been successfully self-assembled on macroscopic scale, forming electrically functional networks (C) (Gracias et al, 2000). Self-assembly dynamics may be simulated on macroscopic scale (D) (Ilievski et al, 2011b).involved. Analogue simulations in the form of a macroscopic self-assembly reactor can act as an alternative, greatly increasing visibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation